2016
DOI: 10.1080/19312458.2016.1150442
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Exposure Opportunities: Using Exogenous Measures in Assessing Effects of Media Exposure on Smoking Outcomes

Abstract: Measurement of exposure has long been one of the most central and fundamental issues in communication research. While self-reported measures remain dominant in the field, alternative approaches such as exogenous or hybrid measures have received increasing scholarly attention and been employed in various contexts for the estimation of media exposure; however, systematic scrutiny of such measures is thin. This study aims to address the gap by systematically reviewing the studies which utilized exogenous or hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 128 publications
0
20
0
Order By: Relevance
“…Several reviews have found evidence that messages delivered through mass media can have small or moderate effects on health behaviors (Naugle & Hornik, 2014;Noar, 2006). However, exposure to messages are self-reported by participants in many of these studies, which may be a major source of bias as respondents are more likely to remember messages that aligned with their prior beliefs or to which they reacted positively (Liu & Hornik, 2016;Prior, 2009). Trials with stronger designs have been equivocal: the design of one trial of a multi-component intervention that demonstrated an effect on handwashing behavior made isolation of the impact of mass media difficult (Curtis et al, 2001), while other trials able to isolate the impact of mass media failed to show a change in handwashing with soap (Chase & Do, 2012;Galiani, Gertler, & Orsola-Vidal, 2012).…”
mentioning
confidence: 99%
“…Several reviews have found evidence that messages delivered through mass media can have small or moderate effects on health behaviors (Naugle & Hornik, 2014;Noar, 2006). However, exposure to messages are self-reported by participants in many of these studies, which may be a major source of bias as respondents are more likely to remember messages that aligned with their prior beliefs or to which they reacted positively (Liu & Hornik, 2016;Prior, 2009). Trials with stronger designs have been equivocal: the design of one trial of a multi-component intervention that demonstrated an effect on handwashing behavior made isolation of the impact of mass media difficult (Curtis et al, 2001), while other trials able to isolate the impact of mass media failed to show a change in handwashing with soap (Chase & Do, 2012;Galiani, Gertler, & Orsola-Vidal, 2012).…”
mentioning
confidence: 99%
“…We calculated the percentage of smokers who made quit attempts attributable to the TFF campaign by taking the difference between the actual quit attempt percentage from the analysis sample and the predicted quit attempt percentage in a hypothetical scenario where exposure to the campaign was 0 for each year of the analysis sample. We then applied these differences in quit attempt rates to corresponding annual state populations of smokers in Florida (18). We performed all statistical analyses using Stata MP version 15.1 (StataCorp LLC).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, literature focuses on measuring news exposure (Bartels, 1993;Liu, Hornik, 2016;Prior, 2009) or various effects of advertising (Freedman, Goldstein, 1999;Taylor et al, 2013). Clearly, the measurement of the ways people are exposed to media content is crucial for the understanding of media use and effects, even though it has been a challenge for a long time.…”
Section: Discussionmentioning
confidence: 99%